Conservation auctions, collusion and the endowment effect - Justin Dijk; Erik Ansink; Daniël Pieter van Soest (Tinbergen Institute, 2018)
We contribute to the literature on the optimal design of auction mechanisms for the procurement of nature conservation activities. We use an economic experiment to examine whether the market efficiency of conservation auctions increases or decreases with repetition. Theory predicts that repetition facilitates collusion among sellers in procurement auctions, while behavioral economics suggests that repetition may increase market efficiency because it attenuates the endowment effect - the phenomenon that ownership of a good tends to increase one's valuation of the good. We find that of these two countervailing effects, the latter has the upper hand; average bids decrease monotonically over the consecutive auctions. Since repetition increases market efficiency, conservation contracts can be of shorter duration and procured at a higher frequency than has been suggested before.
Keywords: C91; D44; H57; Q57; 330; Auctions; procurement; endowment effect; collusion; nature conservation